Variability in the transitions to adulthood in Europe: a critical approach to de-standardization of the life course - Nico, M. (2014)
The concept of de-standardization of the life course is taken for granted in youth research. It has been appropriated by the thesis of individualization, applied almost exclusively to contemporary youth, and mainly established through quali- tative methods and strategies better prepared to approach individual reflexivity and subjectivity, though not necessarily to measure social change. Through a critical approach to the theoretical oscillations and methodological rivalries in the study of this concept, this article uses the European Social Survey data on the organization of the life course to identify and describe various features of the order of the transitions to adulthood over historical time, such as the ratio of biographical combinations per individual, the density and overlapping of the transitions, and the degrees of normativity of the sequences of the transition. Analysis of these partial results allows us to argue that there is not a strong set of evidence for a widespread and general process of de-standardization in Europe as a whole and that in many matters, with important exceptions (such as gender), cross-national heterogeneity is far more significant than differences across generations.